PENGARUH IMUNITAS PEJABAT NEGARA DAN KEBIJAKAN KEUANGAN NEGARA DALAM PENCEGAHAN KKN PADA MASA COVID-19 - Budiyardi; Lu Sudirman; Rufinus Hotmaulana Hutauruk (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
At the end of 2019, it was reported that there was an outbreak of a disease that spread very quickly and was still the Corona Virus Disease 2019 (COVID-19). China officially reported the presence of the corona virus to the World Health Organization (WHO) on December 31, 2019, but a team from Harvard University, by analyzing satellite photos of traffic around a number of hospitals in Wuhan, Hubei Province, China experienced an increase starting last month. August 2019, this may indicate that the corona virus appeared in the city earlier than the reported time frame. As for the problems that will be researched in order to achieve clear and systematic goals and objectives and as desired, the authors limit the problems to be researched so that can answer the question of how the immunity of State Officials in regulating financial policies is reviewed through PERPU 1/2020 in handling Covid-19 and how the influence of PERPU No. 1/2020 and the Constitution against abuse of the authority of state officials in determining financial policy? This research is directed to examine the extent to which PERPU no. 1/2020 can ensure financial stability and the financial system remains safe from threats to the country's economy in the context of handling Covid-19, which is increasingly making the world economy, including Indonesia. The influence of state officials' immunity and state financial policies in preventing KKN during the covid-19 period is very important to be able to help this nation to become a nation that is far from KKN actions and that can be done if the state officials have honesty, truth and justice so as to produce good morality. against state official.